The development of physical comics handout problem based learning to improve students' creative thinking skills in straight motion students - Enny Zarvianti; Desrianti Sahida (Journal of Educational and Learning Studies, 2020)
The development of learning materials from handout by Problem Based Learning (PBL) assisted comics to straight motion of creative thinking skills with valid, practical, and effective has been done. The research and development method is implemented in this work. The 4-D development model was used consist of define, design, development, and disseminate. In the define phase, it was done curriculum, student, and material analysis. In the design phase, it was done by designing learning materials the from handout assisted comics by PBL comprise  learning instructional such as lesson plan (RPP), handout, and assessment. In the development phase, test of validity, practicality, and the effectivity of handout were done. Then in the disseminate phase, test of practicalities and effectiveness were done. The result of the study in the define phase about students was obtained that level of creative thinking skills of students of class X IPA 2 are in the low category. The analysis of material was obtained straight motion. In the design phase, it was obtained initial draft of handout by PBL assisted comics that consist of RPP, handout, and assessment. In the development phase, it was obtained handout by PBL assisted comics which has valid criteria (0,86), practically criteria (94%), and effective for cognitive creative thinking skills aspect (76%), effective in improving creative thinking skills (79%) are in the category of very creative, the category character becomes a habit (86%), and skill was (87%). In the disseminate phase, it was obtained   effective for cognitive creative thinking skills aspect (76,9%), effective in improving creative thinking skills (78,4%) are in the category of very creative, the category character becomes a habit (84%), and skill was (81,9%).